Identificação de áreas de preservação permanente e de conflitos potenciais de uso no setor centro-leste do planalto de Francisco Beltrão - SW/PR - Folador, Benice (2011)
The survey shows permanent preservation areas and use of potential conflicts in the sector East-Central Plateau of Francisco Beltrão, Southwest of Paraná. The analysis was performed based on the recognition of the physical topography and hydrography characteristics as well as the existing land use in the area using geoprocessing techniques. The sectors of APP were individualized according to the Brazilian Forest Code in force. The study area presents 139,061.81 ha, of which 26,515.60 ha are considered environmentally sensitive areas. In accordance with the APP categories analyzed APP (relief elevations, slope above 30°, hydrography), and what the Forest Code defines as APP, 19% of the area study are protected by law. Types of APP in the area studied, the preservation along the waterways accounts for the largest size of protected areas (15,218.93ha). The lowest shares among the APP corresponding to the slopes greater than 45° (2,190.23ha), and APP category Morro (1,155.59 ha). It was identified five classes of land use in central-eastern sector of the Plateau Francisco Beltrão: crops harvested representing 9.20% of total; forest, with 25.43% of the total, urban area 3.05% of the total, crop developing the total 31.88% and 30.43% exposed soil. The conflict areas of use are concentrated along the river bank Chopim and its tributaries near the confluence. The areas of conflict related to the springs channels are distributed randomly across the study area. The APP occupied by forests was considered appropriate use of land and add up to total of 13,103.70 ha. Those areas that were indicated by variables such as topography and hydrography of APP and that the land use analysis showed occupation either with the developing crop, harvested crops, bare soil or urban area, were considered inappropriate land use. These represent the area of 12,128.50 ha in east-central sector of the Plateau Francisco Beltrão.